2016
DOI: 10.1515/afe-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hardener on the Emission of Harmful Substances from Moulding Sands with Furan Resin in the Pyrolysis Process

Abstract: The furan resin offers advantages such as high intensity, low viscosity, good humidity resistance and is suitable for cast different casting alloys: steel, cast iron and non-ferrous metal casting. For hardening furan resins are used different hardeners (acid catalysts). The acid catalysts have significant effects on the properties of the cured binder (e,g. binding strength and thermal stability) [1 -3]. Investigations of the gases emission in the test foundry plant were performed according to the original meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…When phosphoric acid (V) was applied as a hardener, the HAPs emission was app. 3 mg/kg of sand, while it was 10 mg/kg when PTS acid was applied [ 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When phosphoric acid (V) was applied as a hardener, the HAPs emission was app. 3 mg/kg of sand, while it was 10 mg/kg when PTS acid was applied [ 3 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under the influence of the high temperatures of liquid metal, there is a hazard of emitting dangerous substances from a mould: benzene, toluene, ethylbenzene, xylenes (BTEX) and Polycyclic Aromatic Hydrocarbons (PAHs) groups [ 1 ]. The gas evolution performance of the mould is a very important index, which is directly related to the quality of casting [ 2 , 3 , 4 ]. The main reason for testing the emission of compounds from the BTEX or PAHs group is that some of these compounds show carcinogenic and/or mutagenic properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Research work proved that furan resins containing lower than 20% of furfuryl-alcohol provide strongly decreased strength and hot distortion properties to the sand cores. 17 On the other hand, experiments 18,19 showed that the main source of emission gases during the application of sand cores produced with furan and phenolic no-bake processes is mostly derived from the acid catalysts. Because of that, binder manufacturers are forced to develop such binder systems that are characterized by low emissions during the mixing and pouring process while they are providing optimal performance to the sand mixtures.…”
Section: Introductionmentioning
confidence: 99%